One-Carbon Metabolic Pathway Rewiring in Escherichia coli Reveals an Evolutionary Advantage of 10-Formyltetrahydrofolate Synthetase (Fhs) in Survival under Hypoxia - Sah, Shivjee (J Bacteriol, 2015)
In cells, N(10)-formyltetrahydrofolate (N(10)-fTHF) is required for formylation of eubacterial/organellar initiator tRNA and purine nucleotide biosynthesis. Biosynthesis of N(10)-fTHF is catalyzed by 5,10-methylene-tetrahydrofolate dehydrogenase/cyclohydrolase (FolD) and/or 10-formyltetrahydrofolate synthetase (Fhs). All eubacteria possess FolD, but some possess both FolD and Fhs. However, the reasons for possessing Fhs in addition to FolD have remained unclear. We used Escherichia coli, which naturally lacks fhs, as our model. We show that in E. coli, the essential function of folD could be replaced by Clostridium perfringens fhs when it was provided on a medium-copy-number plasmid or integrated as a single-copy gene in the chromosome. The fhs-supported folD deletion (ΔfolD) strains grow well in a complex medium. However, these strains require purines and glycine as supplements for growth in M9 minimal medium. The in vivo levels of N(10)-fTHF in the ΔfolD strain (supported by plasmid-borne fhs) were limiting despite the high capacity of the available Fhs to synthesize N(10)-fTHF in vitro. Auxotrophy for purines could be alleviated by supplementing formate to the medium, and that for glycine was alleviated by engineering THF import into the cells. The ΔfolD strain (harboring fhs on the chromosome) showed a high NADP(+)-to-NADPH ratio and hypersensitivity to trimethoprim. The presence of fhs in E. coli was disadvantageous for its aerobic growth. However, under hypoxia, E. coli strains harboring fhs outcompeted those lacking it. The computational analysis revealed a predominant natural occurrence of fhs in anaerobic and facultative anaerobic bacteria.